Macrophage PKM2 depletion ameliorates hepatic inflammation and acute liver injury in mice - Kang, Ziwei; Xie, Ruoyan; Cui, Yiming; Chen, Zhiwei; Li, Jincheng; Lv, Jinyu; Ye, Weijia; Zhao, Peixin; Zhang, Keke; Hong, Jian; Qu, Hengdong (Frontiers in Pharmacology, 2025)
Introduction:Pyruvate kinase M2 (PKM2), the rate-limiting enzyme of glycolysis, plays a critical role in macrophage activation and a broad spectrum of chronic liver diseases. However, whether PKM2 contributes to the pathogenesis of acute liver injury (ALI) remains largely unexplored.MethodsPKM2 expression was assessed in human and mouse ALI livers. Macrophage-specific PKM2 knockout mice were challenged by two independent ALI models, induced by acetaminophen (APAP) and lipopolysaccharide/D-galactosamine (LPS/D-GalN), to explore the role and regulatory mechanism of macrophage PKM2 in ALI progression.ResultsBy bioinformatic screening and analysis of ALI liver, we found that PKM2 was significantly upregulated in the liver tissues of ALI patients and mice. Immunofluorescence staining further demonstrated that PKM2 was markedly upregulated in macrophages during ALI progression. Notably, macrophage PKM2 depletion effectively alleviated APAP- and LPS/D-GalN-induced ALI, as demonstrated by ameliorated immune cells infiltration, pro-inflammatory mediators, and hepatocellular cell death. PKM2-deficient macrophages showed M2 anti-inflammatory polarization in vivo and in vitro. Furthermore, PKM2 deletion limited HIF-1α signaling and aerobic glycolysis of macrophages, which thereby attenuated macrophage pro-inflammatory activation and hepatocyte injury. Pharmacological PKM2 antagonist efficiently ameliorated liver injury and prolonged the survival of mice in APAP-induced ALI model.Discussion:Our study highlights the pivotal role of macrophage PKM2 in advancing ALI, and therapeutic targeting of PKM2 may serve as a novel strategy to combat ALI.